Copper Nanoparticles Synthesized in Biopolymer Matrix and Their Application in Antibacterial Activity - Aminu Musa; Ameen Hadi Mohammed; Mansor Ahmad; Monday Musah (مجلة بغداد للعلوم, 2024)
Copper is a cheaper alternative to various noble metals with a range of potential applications in the field of nanoscience and nanotechnology. However, copper nanoparticles have major limitations, which include rapid oxidation on exposure to air. Therefore, alternative pathways have been developed to synthesize metal nanoparticles in the presence of polymers and surfactants as stabilizers, and to form coatings on the surface of nanoparticles. These surfactants and polymeric ligands are made from petrochemicals which are non- renewable. As fossil resources are limited, finding renewable and biodegradable alternative is promising.The study aimed at preparing, characterizing and evaluating the antibacterial properties of copper nanoparticles. Copper nanoparticles were prepared using gelatin biopolymer, CuSO4.5H2O ions and hydrazine as stabilizer, precursor salt and reducing agent respectively. However, vitamin C and NaOH solution were also employed as an antioxidant and pH adjuster. The synthesized copper nanoparticles were characterized using UV-visible spectroscopy (UV-vis), thermogravimetric analysis (TGA), zeta potential measurements powder, X-ray diffraction (XRD), field emission scanning electron microscope and transmission electron microscope (TEM). The UV-visible absorption spectrum confirms the formation of the CuNPs, which showed maximum absorbance at 583 nm. Results obtained from TEM indicated a decrease in size of particle from a low concentration to high concentration of the supporting materials. The optimum concentration of gelatin was found to be 0.75 wt%. The supporting materials used for this synthesis are biocompatible and the obtained products are stable in air. The synthesized CuNPs display promising antibacterial activities against B. subtilis (B29), S. aureus (S276), S. choleraesuis (ATCC 10708) and E. coli (E266) as gram positive and negative bacteria respectively.